2007
DOI: 10.1021/jp074088f
|View full text |Cite
|
Sign up to set email alerts
|

Formation of Active Sites in TS-1 by Hydrolysis and Inversion

Abstract: The interaction of water molecules with Ti sites in titanium silicalite has been studied using a hybrid quantum mechanical/molecular mechanical approach. We have examined the structure and stability of a number of structurally different sites, many of which are based on the hydrolysis and inversion of tetrahedral sites in the zeolitic framework. The hydration of all considered Ti centers is found to be exothermic, which is in good agreement with experiment and previous theoretical work. Under such conditions, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 39 publications
0
17
0
Order By: Relevance
“…The study showed that while hydrolysis of the first TiOSi bond is energetically favorable, further hydrolysis steps are highly endothermic. [93] However, in the case of tin, hydrolysis of the first SnO(Si) bond was found to be mildly endothermic (20-40 kJ mol −1 with reaction barriers between 75 and 100 kJ mol −1 ) as reported by two recent computational works employing periodic DFT calculations. [94] Another experimental study focusing on partial hydrolysis of titano-and stanno-silicates was reported by Yakimov et al They followed the time evolution of the 119 Sn MAS NMR spectra of a dehydrated Sn-BEA sample exposed to gas-phase water (4 H 2 O per Sn) at ambient temperature and reported that penta-coordinated tin gradually transformed into the hexa-coordinated state at long contact times (from several hours up to a month, depending on the strength of the particular tin Lewis acid site).…”
Section: Partial Hydrolysis Of Tin and Titanium Sites In Zeolitesmentioning
confidence: 76%
See 1 more Smart Citation
“…The study showed that while hydrolysis of the first TiOSi bond is energetically favorable, further hydrolysis steps are highly endothermic. [93] However, in the case of tin, hydrolysis of the first SnO(Si) bond was found to be mildly endothermic (20-40 kJ mol −1 with reaction barriers between 75 and 100 kJ mol −1 ) as reported by two recent computational works employing periodic DFT calculations. [94] Another experimental study focusing on partial hydrolysis of titano-and stanno-silicates was reported by Yakimov et al They followed the time evolution of the 119 Sn MAS NMR spectra of a dehydrated Sn-BEA sample exposed to gas-phase water (4 H 2 O per Sn) at ambient temperature and reported that penta-coordinated tin gradually transformed into the hexa-coordinated state at long contact times (from several hours up to a month, depending on the strength of the particular tin Lewis acid site).…”
Section: Partial Hydrolysis Of Tin and Titanium Sites In Zeolitesmentioning
confidence: 76%
“…The study showed that while hydrolysis of the first TiOSi bond is energetically favorable, further hydrolysis steps are highly endothermic. [ 93 ] However, in the case of tin, hydrolysis of the first SnO(Si) bond was found to be mildly endothermic (20–40 kJ mol −1 with reaction barriers between 75 and 100 kJ mol −1 ) as reported by two recent computational works employing periodic DFT calculations. [ 94 ] Another experimental study focusing on partial hydrolysis of titano‐ and stanno‐silicates was reported by Yakimov et al.…”
Section: Reactive Interaction Of Water With Zeolitesmentioning
confidence: 82%
“…Computational studies showed that the formation of the first Ti-OH group stabilized the metal ion in the framework, while further hydrolysis of Ti-O-Si bonds was energetically unfavourable. 28 There is theoretical and experimental evidence for the formation of 'open' sites also for Sn-and Zr-containing zeolites. 29…”
Section: Lewis Acid Centresmentioning
confidence: 99%
“…The most detailed study addressing these problems was reported by To et al, 440,441 who used QM/MM techniques to model Ti substitutional centers in silicalite. The most detailed study addressing these problems was reported by To et al, 440,441 who used QM/MM techniques to model Ti substitutional centers in silicalite.…”
Section: View Article Onlinementioning
confidence: 99%